Engaging nurses to strengthen medication safety: Fostering and capturing change with restorative photographic research methods. Issue 6 (14th April 2014) - Gimenes, Fernanda Raphael Escobar; Marck, Patricia Beryl; Atila, Elisabeth Gulden; Cassiani, Silvia Helena de Bortoli
Abstract : We used participatory photographic research methods adapted from the field of ecological restoration to engage Brazilian intensive care unit nurses in a critical review of medication safety in their work environment. Using focus groups, practitioner‐led photo walkabouts with photo narration, and photo elicitation focus groups in iterative phases of data collection and analysis, nurses developed and implemented several practical and cultural improvements for their unit. Participants focussed on organizing the medication room for efficient workflow and accessible supplies, improving reporting practices, and reconsidering how they could manage safety issues in their unit and in the hospital as a whole. Our results demonstrated that restorative photographic research methods enabled participants to (re)think and redesign their work environment in keeping with several recommended practices for improving medication management. It also validated the need for continuous evidence‐informed improvements if nurses hope to optimize medication safety in the complex systems of intensive care.